Проблеми формування системи управління збутовою діяльністю: експортний вектор - Завербний, А. С.; Псуй, М. С.; Пушак, Г. І.; Zaverbnyi, A.; Psyj, M.; Pushak, G. (Видавництво Львівської політехніки, 2018)
У статті проаналізовано проблеми формування системи управління збутовою діяльністю. Виокремлено проблеми, з якими стикатимуться національні виробники в умовах відкритості економіки, євроінтеграції. На основі проведеного аналізування наукових досліджень вітчизняних, зарубіжних вчених виділено та розглянуто основні методи управління збутовою діяльністю в умовах виходу на зовнішні ринки збуту.

The issue of sales produced by the national producer of products becomes great importance in the context of European integration. This applies not only to exports. The gradual liberalization of foreign trade policy will align the working conditions of domestic and foreign producers. The article is devoted to the problems of forming a systemof sales management. The purpose of this article is the study the problems of the formation the management system sales activities of the export direction in the context of European integration. Results of the research. The main goals of the sales activities of enterprises are derivatives of its general. The main components of the sales of enterprises are systems, forms, channels of sales. The ratio of these elements of parts in certain market situations will allow national commodity producers to effectively realize the relevant marketing goals. Enterprises should take into account, developing a system for managing sales activities, that it should correspond to the main activities. The most important factors necessary for the success of national enterprises must be progressiveness, foresight, focus on the prospect of the top management according to market conditions, economic integration. This is possible provided the professional formation of a flexible and efficient sales management system is possible. Conclusions. The correct separation of the market segment will ensure a high level of efficiency of sales activities. Segmentation of the market has an advantage. All resources of the enterprise can be concentrated on the most perspective segments (markets). This will allow you to plan the volume of production, sales of goods that meet specific demand. This will help to select the appropriate means of communication, in coordination with the target segment (market). This is a way to optimize your marketing costs, and more. It is necessary to formulate plans for this activity for the effective planning of sales activities. These plans should be based on forecast data relating to the market segment in which the company operates, sales management systems, its elements, etc. The development of forecast models should be carried out in accordance with the main methodological forecasting principles. The organization of sales activity is a part of the functional subsystem of the enterprise. It should provide for the coordination of workers who carry out comprehensive work on management of marketing operations. Sales organization should include the selection of specialists to all sales divisions, the assessment of the quality level, the effectiveness of work, measures for material, moral motivation, etc.
Problems of formation of sales manadgment systems: export vector
Keywords: збут; система управління збутовою діяльністю; експорт; експортна діяльність; sales; marketing management system; export; export activity; 303.823.3; 339.564; 658.7; 658.8.012.12